Herpes Simplex Virus 1 Small Noncoding RNAs 1 and 2 Activate the Herpesvirus Entry Mediator Promoter - Tormanen, Kati; Wang, Shaohui; Matundan, Harry H.; Yu, Jack; Jaggi, Ujjaldeep; Ghiasi, Homayon (Journal of virology, 2022)
HSV-1 causes recurrent ocular infections, which is the leading cause of corneal scarring and blindness. Corneal scarring is caused by the host immune response to repeated reactivation events. Herpes simplex virus 1 (HSV-1) latency-associated transcript (LAT) plays a significant role in efficient establishment of latency and reactivation. LAT has antiapoptotic activity and downregulates expression of components of the type I interferon pathway. LAT also specifically activates expression of the herpesvirus entry mediator (HVEM), one of seven known receptors used by HSV-1 for cell entry that is crucial for latency and reactivation. However, the mechanism by which LAT regulates HVEM expression is not known. LAT has two small noncoding RNAs (sncRNAs) that are not microRNAs (miRNAs), within its 1.5-kb stable transcript, which also have antiapoptotic activity. These sncRNAs may encode short peptides, but experimental evidence is lacking. Here, we demonstrate that these two sncRNAs control HVEM expression by activating its promoter. Both sncRNAs are required for wild-type (WT) levels of activation of HVEM, and sncRNA1 is more important in HVEM activation than sncRNA2. Disruption of a putative start codon in sncRNA1 and sncRNA2 sequences reduced HVEM promoter activity, suggesting that sncRNAs encode a protein. However, we did not detect peptide binding using two chromatin immunoprecipitation (ChIP) approaches, and a web-based algorithm predicts low probability that the putative peptides bind to DNA. In addition, computational modeling predicts that sncRNA molecules bind with high affinity to the HVEM promoter, and deletion of these binding sites to sncRNA1, sncRNA2, or both reduced HVEM promoter activity. Together, our data suggest that sncRNAs exert their function as RNA molecules, not as proteins, and we provide a model for the predicted binding affinities and binding sites of sncRNA1 and sncRNA2 in the HVEM promoter. IMPORTANCE HSV-1 causes recurrent ocular infections, which is the leading cause of corneal scarring and blindness. Corneal scarring is caused by the host immune response to repeated reactivation events. LAT functions by regulating latency and reactivation, in part by inhibiting apoptosis and activating HVEM expression. However, the mechanism used by LAT to control HVEM expression is unclear. Here, we demonstrate that two sncRNAs within the 1.5-kb LAT transcript activate HVEM expression by binding to two regions of its promoter. Interfering with these interactions may reduce latency and thereby eye disease associated with reactivation.